Advances in chemical physics (Hohn Wilet & Son, 2003)
The latest edition of the leading forum in chemical physics. Edited by Nobel Prize winner Ilya Prigogine and renowned authority Stuart A. Rice, the Advances in Chemical Physics series provides a forum for critical, authoritative evaluations in every area of the discipline. In a format that encourages the expression of individual points of view, experts in the field present comprehensive analyses of subjects of interest. Volume 126 covers a wide range of subjects, with significant, up-to-date chapters by internationally recognized researchers. The editors collect innovative papers on "Calculations of Nonlinear Optical Properties for the Solid State," "Itinerant Oscillator Models of Fluids," "Statistical Mechanics of Static and Low-Velocity Kinetic Friction," and several other related topics. Advances in Chemical Physics remains the premier venue for presentations of new findings in its field